The Evaluation of Project-Based Learning at the Mechanical Engineering Department, Polytechnic Malaysia: A Prosess Dimension Assessment - Sadrina Sadrina; Ramlee Mustapha (PTE FTK UIN Ar-Raniry, 2017)
The purpose of the study was to evaluate the effectiveness of Project-Based Learning in the Mechanical Engineering Department at the Polytechnic in Malaysia. This study was designed with Context, Input, Process and Product (CIPP) model. Project-Based Learning is a different approach than the traditional learning in the sense that it is a student-centered learning approach based on the principles of constructivism. This study involved a random sample of 118 students and 43 supervisors in the Mechanical Engineering Department in Polytechnic Kota Bharu Malaysia. The instrument used in this study were a set of questionnaire. In terms of finding ideas, both students and supervisors agreed that students were encouraged to assess the real problem by their supervisors. However, the supervisors were uncertain whether the students went to the library to get the ideas for their project. In addition, the supervisors were barely agreed about the creativity of the students in finding the project ideas. However, students and their supervisors believed that critical thinking and creativity were needed in the Project-Based Learning. The respondents also believed that e-SOLMS helped the students to work in group to complete the project.